Hak Pendidikan dalam Menunjang Kreativitas Siswa - Muhammad Rezki Aditya Perdana; Zeha Dwanty El Rachma; Erika Sabrina; Tomy Michael (LITERATUS, 2020)
The research objective is to determine what factors make the cost of education in Indonesia increase, optimization in terms of facilities in each school and the suitability of funds issued from the government is optimal for each educational institution. The research method uses empirical legal research methods. Empirical legal research is a law that is conceptualized as an empirical symptom of the extent to which it carries out its duties, principal, and functions in its implementation or reality in society. One of the significant forms of funding for basic education from the State Budget (APBN) funding source is BOS funds. To start the budget, several things are carried out starting from budget planning, budget implementation, education financial administration, monitoring of the education budget..